Phyotherapy in gynecological infections as natural support in the treatment process - Grzesik-Gąsior, Joanna; Bień, Agnieszka; Pieczykolan, Agnieszka (Nursing in the 21st Century, 2018)
PHYOTHERAPY IN GYNECOLOGICAL INFECTIONS AS NATURAL SUPPORT IN THE TREATMENT PROCESSIntroduction. Phytotherapy is a part of the science of medicinal plants – it includes the prevention and treatment of various disorders with the help of plants and their parts (including seeds, leaves, roots, flowers and fruits), active substances extracted from them and plant preparations’ the formula of herbal medicines goes back to ancient times. Herbal medicine should complement or strengthen synthetic therapy, not being its alternative. Phytotherapy in obstetrics and gynecology is a far-reaching procedure. The beneficial effects of plant preparations are used, inter alia, in cases of inflammation of the urinary tract, vaginitis and vulva, premenstrual syndrome, menstrual disorders, climacteric syndrome and in the postpartum period (e.g. in the healing of crotch injuries and problems with lactation).Aim. Presentation the action of selected natural products in the treatment of urinary tract infections, bacterial vaginosis, vaginal and vulva candidiasis and human papillomavirus infection (HPV).